Developmental changes in bicuspid aortic valve and associated aortopathy in small children. (14th October 2021) - Boesgaard Norsk, J; Sillesen, A S; Axelsson Raja, A; Munk Paerregaard, M; Pihl, C; Voegg, R O B; Vejlstrup, N; Iversen, K; Bundgaard, H
Abstract: Background: The prevalence of bicuspid aortic valve (BAV) in newborns is 0.8%. BAV is associated with an increased risk of aortic valve dysfunction and aortopathy. Aortopathy with increased aortic diameters has recently been reported in newborns with BAV. As most patients with BAV are diagnosed in adulthood the development of BAV and associated aortopathy during early years of life is not well described. Purpose: The purpose of the study was to assess changes in aortic valve function and aortic dimensions at two to four years of age in children diagnosed with BAV neonatally. Methods: Children with BAV were included from a population-based cohort study, in which newborns (n≈25, 000) underwent standardized transthoracic echocardiography (TTE). Follow-up TTE was performed and analyzed according to established guidelines. Neonatal (baseline) and follow-up data were compared. Diameters were indexed to body surface area (BSA). Z-scores were calculated using formulas from the Pediatric Heart Network Echocardiogram Database. Results: At follow-up 101 newborns with BAV (mean age 2 years 5 months, SD 11 months), 75% male) were examined from May 2019 to April 2021. From baseline to follow-up there was an increase in the BSA-adjusted diameter of the aortic valve annulus (z-score −0.19 at baseline vs 0.95 at follow up, p<0.001), and of the sino-tubular junction (z-score 0.16 at baseline vs 0.43 at follow up, p<0.05). Conversely, there was a decrease in the Z-score for the diameter measured 1 cm from the valve annulus (z-score 1.31 at baseline vs 0.68 at follow up, p<0.001) and at the widest point of the visualized ascending aorta (z-score 2.44 at baseline vs 1.45 at follow up, p<0.001). There was no significant change in the diameter of the sinus of Valsalva (z-score 0.83 at baseline vs 0.80 at follow up, p=0.92). The number of children with at least one aortic z-score >3 was 31 (30.6%) at baseline and 17 (17.8%) at follow up. At baseline mild aortic valve regurgitation was observed in 18 children (17.8%) and in 23 children at follow up (23%). Mean maximum systolic velocities across the aortic valve were 1.03 m/s at baseline (SD 0.24) and 1.11 m/s at follow up (SD 0.27), p<0.05. Aortic stenosis, defined as flow velocity >2.5 m/s was seen in one child both at baseline and at follow-up. Conclusion: In children diagnosed with BAV neonatally, re-examination at the age of 2.5 years showed significant increases in the diameter of the aortic valve annulus and the sino-tubular junction, but a significant decrease in the diameter of the ascending aorta. The maximum blood flow velocity across the aortic valve increased and more children had developed mild aortic valve regurgitation. Thus, the bicuspid aortic valve and the associated aortopathy seem to undergo remodeling during early childhood. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Danish Children's Heart Foundation, Boernehjertefonden.